2022
DOI: 10.1177/26350106221136495
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Opt-In: A Randomized Controlled Pilot Study to Improve Sleep and Glycemic Variability in Adults With Type 1 Diabetes

Abstract: Purpose: The purpose of this study was to evaluate the feasibility and acceptability of a technology-assisted behavioral sleep intervention (Sleep-Opt-In) and to examine the effects of Sleep-Opt-In on sleep duration and regularity, glucose indices, and patient-reported outcomes. Short sleep duration and irregular sleep schedules are associated with reduced glycemic control and greater glycemic variability. Methods: A randomized controlled parallel-arm pilot study was employed. Adults with type 1 diabetes (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…Analisando todos os artigos coletados foi possível constatar que o sono e os níveis glicêmicos de pacientes diabéticos estão diretamente relacionados, uma vez que um sono insuficiente com baixa qualidade afeta negativamente o índice glicêmico, tanto da diabetes tipo 1 quanto a do tipo 2. Além disso, como afirma o estudo de MARTYN-NEMETH, P. et al (2023), a melhora na regularidade do sono ao longo do período de 8 semanas contribuiu para a melhora dos índices glicêmicos dos participantes do estudo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Analisando todos os artigos coletados foi possível constatar que o sono e os níveis glicêmicos de pacientes diabéticos estão diretamente relacionados, uma vez que um sono insuficiente com baixa qualidade afeta negativamente o índice glicêmico, tanto da diabetes tipo 1 quanto a do tipo 2. Além disso, como afirma o estudo de MARTYN-NEMETH, P. et al (2023), a melhora na regularidade do sono ao longo do período de 8 semanas contribuiu para a melhora dos índices glicêmicos dos participantes do estudo.…”
Section: Discussionunclassified
“…Ante a esse quadro, revela-se que distúrbios do sono (sono irregular ou insuficiente) são determinantes a resistência a insulina, variabilidade glicêmica e aumentos da hemoglobina média A1C (A1C). Além disso, observa-se uma relação bidirecional, entre o sono e a glicemia no DT1, uma vez que as variações glicêmicas, hipoglicemia e as intervenções terapêuticas para essa doença, impactam nos aspectos do sono (NEMETH et al, 2023).…”
Section: Introductionunclassified
“…Sleep education combined with diabetes education in patients with diabetes who were late sleepers led to a greater reduction in IL‐6 than diabetes education alone; the improvement of which correlated with a reduction in A1C (Li et al, 2018). A pilot study in type 1 diabetes utilised technology‐assisted behavioural intervention targeting those with irregular and/or short sleep (Martyn‐Nemeth et al, 2022). The intervention group showed an improvement in sleep regularity (day‐to‐day variations of sleep midpoint) and glucose levels compared with a health education control group, although inflammatory markers were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…For 8 weeks, individuals in the Sleep-Opt-In group had access to digital lessons, a sleep tracker, and weekly phone calls from a trained sleep coach. Afterward, they assessed the feasibility of Sleep-Opt-In and its effects on sleep duration, sleep regularity, glycemic parameters, and patient-reported outcomes [ 73 ]. The study results revealed that irregular sleep was a greater problem than insufficient sleep.…”
Section: Introductionmentioning
confidence: 99%
“…The study results revealed that irregular sleep was a greater problem than insufficient sleep. The Sleep-Opt-In intervention led to improved sleep regularity, improved glucose parameters (CV% and time-in-range), reduced fatigue, and enhanced mood [ 73 ], suggesting that individuals with type 1 diabetes and irregular sleep may benefit from sleep optimization interventions.…”
Section: Introductionmentioning
confidence: 99%